Evoked potentials in Guillain-Barré syndrome - Topçu, Meral; Ergin, Murat; Nurlu, Gülay; Renda, Yavuz; Kanra, Güler; Seçmeer, Gülten (The Turkish Journal of Pediatrics, 1993)
A prospective evaluation was made in a total of 19 patients with Guillain-Barré syndrome (GBS) by neurologic examination, visual evoked potentials (VEP), brain-stem auditory evoked potentials (BAEP) and somatosensory evoked potentials (SEP) during the acute phase of the disease, three weeks later, and then again three months after the onset of symptoms. The results of electrophysiologic studies of the patients were compared with those of 19 healthy children. There were no statistically significant differences found in the mean VEP and BAEP values between the patient and control groups. However, the VEP and BAEP values were abnormal during the first and second stages of the disease in only a few patients. There was a statistically significant prolongation of the response in tibial and median SEP during the first and second stages of the disease when compared with the third stage and the control group. The Erb-Cervical 7 (C7) interwave latency was elevated in the median SEP. It was concluded that the prolongation of the response in SEP was diagnostically important in the acute phase of GBS. There was no correlation found between SEP and clinical progression.
Keywords: evoked potentials; Guillain-Barré syndrome